Long-term virologic responses to responses to antiretroviral therapy among patients entering adherence clubs in Khayelitsha, Cape Town South Africa - Kehoe, Kathleen (Department of Public Health and Family Medicine, 2019)
Introduction: In 2017, approximately 36.9 million people were living with HIV and 58.1% were accessing antiretroviral therapy (ART) worldwide. In South Africa, ART coverage was 48.6% in 2015, and has since increased due to the implementation of universal Test and Treat. Given the need for lifelong care for millions of individuals, differentiated models of care for ART services are required. One such model, adherence clubs (ACs) for stable ART patients, has been successfully scaled-up in the Cape Metro Health District. In this study, we describe long-term virologic outcomes of patients who have ever entered ACs. Methods: Adult patients enrolled in ACs in Khayelitsha between January 2011 and June 2017 were eligible for inclusion. Time to, and risk factors for, an elevated viral load (first viral load >1000 copies/mL) and confirmed virologic failure (two consecutive viral loads >1000 copies/mL two to nine months apart) were estimated using the Kaplan-Meier estimator and Cox proportional hazards models. Viral load completeness was assessed at 4, 16, 28, 40 and 52 months of follow up. Results: Of 11 830 patients, 74% were female and 45% were aged 35-44 years at AC enrolment. The median time on ART at enrolment was 4.7 years (interquartile range (IQR) 2.7-7.1). An elevated viral load was observed in 517 patients (4%), 141 (27%) of whom subsequently experienced confirmed virologic failure. The median time from an elevated viral load to confirmed virologic failure was 137 days (IQR 112-168). Risk of an elevated viral load and confirmed virologic failure was higher among patients with a longer duration on ART and lower among older patients. The proportion of completed viral load tests ranged from 79% at 4 months to 75% at 52 months. Over 90% of patients with viral load assessments remained virologically suppressed (<400 copies/mL). Conclusion: This study demonstrates low rates of confirmed virologic failure among patients who entered ACs. The majority of patients remained stable despite the rapid growth of ACs, supporting the continued expansion of the model, particularly for men. Monitoring was generally consistent, but suboptimal among those who experienced an elevated viral load. Patients referred to ACs, younger patients and those with longer duration of ART should be prioritised to ensure they remain stable on lifelong ART.